Faust/yna. W promieniach Artura Pałygi - Kopiciński, Jacek (Załącznik Kulturoznawczy, 2023)
In this essay, author deals with the interpretation of a very original, new monodrama by Artur Pałyga, entitled In Radiance (2016), whose heroine is Maria Skłodowska-Curie. The author is interested in a poetic and performative dimension of Maria’s dozen monologues, which the author described as − completely unknown letters’ of the scientist. These monologues reveal the process of Maria’s spiritual development from the moment of attainingmaturity, until her death due to excessive irradiation. Kopciński focuses on the aspects of Maria’s consciousness, which Pałyga has brought forth from the myth of Faust, which comprises the foundation of the scientific worldview. In this monodrama, Skłodowska-Curie is the Polish Faust, who is ready to break the moral rules and pay the price of her and others’ life for sheer possibility of revealing the mystery of the universe. Kopciński confronts this original literary image of a scientist with the history of her life and highlights the moments in her biography that can be read as an execution of the ‘Faustian bargain’. At the end of his work he compares the character of Skłodowska-Curie, who calls herself Faustina, with the figure of another, extraordinary woman who has also adopted this name − Maria Faustina Kowalska. The comparison of the scientist and the mystic woman allows us to see many similarities in the characters of both, their way of life and their relationships with other people, but also describe fundamental differences in the worldviews they represent. Finally, two Faustinas are two different symbols. The figure of a scientist symbolizes desire for intellectual control over the world, which is constantly changing like elements discovered by Maria Skłodowska. On the other hand, the figure of the mystic symbolizes desire for an inner union with loving God, which involves the sacrifice of one’s ‘self’ to gain eternal life of the immortal soul.